Implementasi Model Pembelajaran Kooperatif Learning terhadap Materi Akidah Akhlak Di Mi NU Suryawiyyah - Velly Desi Ayu Fatimah; Farid Khoeroni; Sanusi Sanusi (Universitas Hamzanwadi, 2025)
Abstract The research is aim to analysis the implementation of the implementation of the Cooperative Learning learning model to the Akidah Akhlak materials at one of the educational institutions in Mejobo, Kudus. This research used a descriptive qualitative research method with data collection through reflection, interviews, field research, and literature searches or online studies that support the research. The data analysis method is carried out using the analytical descriptive method through data reduction, data presentation, and finding conclusions. The results of this research stated that the application of the Cooperative Learning learning model on the Akidah Akhlak materias was able to encourage students' enthusiasm for learning to improve student learning achievement in learning Akidah Akhlak, this was indicated by a positive response from students after a trial of the application of the Cooperative Learning learning model on learning Akidah Akhlak. The implementation of the Cooperative Learning learning model that was carried out did not face significant obstacles, it's just that there were several groups of students who had not experienced following active learning models such as cooperative learning so that they had the potential to experience difficulties in the learning process, especially in making mind mapping. Kata kunci: Akidah Akhlak Material, Learning Models, Cooperative Learning Abstrak Penelitian ini berorientasi pada analisis implementasi model pembelajaran Kooperatif pada pembelajjaran materi Akidah Akhlak di salah satu Lembaga pendidikan di Mejobo, Kudus. Penelitian ini memanfaatkan metode penelitian kualitatif deskriptif melalui pengumpulan data observasi, wawancara, penelitian lapangan, dan penelusuran literatur atau kajian online yang mendukung penelitian. Metode analisis data dilakukan dengan metode deskriptif analitik melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ditemukan bahwa implementasi model pembelajaran Kooperatif Learning pada materi pembelajaran Akidah Akhlak mampu endorong semangat belajar siswa hingga meningkatkan prestasi belajar siswa dalam pembelajaran Akidah Akhlak, hal tersebut ditandai dengan adanya respon positif dari siswa setelah dilakukan uji coba penerapan model pembelajaran Kooperatif pada pembelajaran Akidah Akhlak. Implementasi penerapan model pembelajaran Kooperatif yang dilakukan tidak menghadapi kendala yang berarti, hanya saja terdapat beberapa sekelompok siswa yang belum berpengalaman mengikuti model pembelajaran aktif seperti kooperatif learning sehingga berpotensi mengalami kesulitan dalam proses pembelajaran utamanya dalam pembuatan mind mapping. Kata kunci: Materi Akidah Akhlak, Model Pembelajaran, Kooperatif Learning